2010
DOI: 10.1097/sla.0b013e3181fd36a2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Delay and Survival After Surgery for Cancer of the Pancreatic Head With or Without Preoperative Biliary Drainage

Abstract: In patients with pancreatic head cancer, the delay in surgery associated with PBD does not impair or benefit survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
105
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 36 publications
7
105
2
4
Order By: Relevance
“…Although only scattered data are available on early outcome after PD following severe post-ERCP pancreatitis [14], there are no reports on late outcome. It seems that preoperative biliary drainage and the delay in surgery do not adversely affect late outcome, with median survival time for resected periampullary adenocarcinoma of 44.7 months [15]. However, the occurrence of complications related to preoperative biliary drainage or surgery was found to be significantly associated with worse survival [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although only scattered data are available on early outcome after PD following severe post-ERCP pancreatitis [14], there are no reports on late outcome. It seems that preoperative biliary drainage and the delay in surgery do not adversely affect late outcome, with median survival time for resected periampullary adenocarcinoma of 44.7 months [15]. However, the occurrence of complications related to preoperative biliary drainage or surgery was found to be significantly associated with worse survival [15].…”
Section: Discussionmentioning
confidence: 99%
“…A randomised trial of preoperative biliary drainage in pancreatic head tumours did not show any advantage to preoperative stenting 14 and an 'early surgery' policy may also be beneficial in hilar cholangiocarcinoma. The perioperative mortality rate of our group (14%) is difficult to compare with that of other series owing to the low sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it is obviously excessive if PD is applied for localized adenoma with low-grade dysplasia [1][2][3][4] . In other words, an inappropriate choice of treatment procedure would have a markedly larger impact on the clinical course in patients with ampullary lesions than in patients with early gastric or colonic cancer, both of which are often treated endoscopically [1][2][3][4][16][17][18] ; thus, accurate preprocedural diagnosis is essential for avoiding such an inappropriate choice. However, the reported false-negative rate of endoscopic biopsy for cancer in ampullary lesions is high at 12 60 4,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is difficult to state that EP is an established treatment procedure. In addition, it has been reported that preoperative biliary drainage causes significant fibroproliferative inflammatory changes in bile ducts, making dissection difficult on performing PD 16 and increasing the complication rate after PD [16][17][18] . EP is obviously a more complicated procedure and thus considered to adversely affect the adjacent tissues more than biliary stenting alone, suggesting that PD following ampullectomy could be more technically difficult than PD without prior ampullectomy.…”
Section: Discussionmentioning
confidence: 99%